NORMOPROJECT ACTIVITY: APPROACHES TO UNDERSTANDING, PRINCIPLES OF IMPLEMENTATION AND WAYS OF IMPROVEMENT - Tarakhonych, Tetiana; Parkhomenko, Nataliia (European Science, 2025)
The section defines the concept of rulemaking as a kind of legal activity to create an integrated system of regulatory legal acts by authorized state entities within the framework of procedurally defined requirements and in compliance with the rules of r